How sustainable is sustainable wildlife tourism? - Brett, Michael R., author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
The first formal protected area in Africa was proclaimed in June 1894 in the Zuid-Afrikaansche Republiek (ZAR). This protected area was followed four years later by the forerunner of the Kruger National Park. In 1926 the second national park in Africa was proclaimed in the eastern Lowveld of South Africa, and named after Paul Kruger, a former president of the ZAR. In the following year a total of three cars visited the park, and by 1979 visitors had increased to 400,000 per annum. Visitor numbers doubled from 1956 to 1963, between 1963 and 1980, and from 1980 to 1995. In 2014 a total of 1.6 million visitors entered the national park. Of this figure, day visitors comprise77 percent of the total. Visitor facilities in the Kruger National Park currently comprise 4048 beds and 653 campsites in 25 rest camps, 805 kilometers of tarred roads and 1720 kilometers of gravel roads. Since 2002 a total of 334 beds in 17 concession lodges have been added. Visitor numbers are increasing at between 6 and 7 percent per annum, and will double within 11 to 12 years. During peak holiday periods, this equates to 2.5 overnight visitors per km of road, compared to 1.4 overnight visitors per kilometre for Hluhluwe-iMfolozi Game Reserve. In the southern half of the Kruger Park, where 70 percent of accommodation is concentrated, densities increase to 2.97 overnight visitors per km of road. Given the rapid increase in accommodation in the past years, the question should be asked if this is sustainable. Will the Kruger Park be able to accommodate 3.2 million visitors by 2025 and 6.4million visitors by 2036?Can the national park continue absorbing increasing numbers of visitors and what will the environmental impact be of such an action? Can wildlife tourism be sustainable when human populations and economies continue to grow? If accommodation and roads cannot be extended indefinitely, what, then, are the alternatives? Are there too many visitors, or is the problem one of inadequate management of visitors? And what lessons can be learned from high-density tourism destinations in other parts of the world? Can government be expected to establish new protected areas and visitor facilities in countries where there are so many urgent socio-economic needs? And what role can private protected areas and game ranches play in meeting the growing demand for nature-based tourism? This paper examines these issues and proposes a course of action for the future.
How sustainable is sustainable wildlife tourism? Examples from protected areas in South Africa
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.